2019
DOI: 10.1038/s41523-019-0136-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a causal role by mouse mammary tumour-like virus in human breast cancer

Abstract: We have reviewed the evidence relevant to mouse mammary tumour viruses (MMTV) and human breast cancer. The prevalence of MMTV-like gene sequences is 15-fold higher in human breast cancer than in normal human breast tissue controls and is present in up to 40% of human breast cancers. MMTV-like gene sequences can be identified in benign breast tissues 1-11 years before the development of positive MMTV-like breast cancer in the same women. The prevalence of MMTV antibodies in sera from women with breast cancer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…Reviews of case control studies of viruses and breast cancer have been previously conducted. These include (i) MMTV by Lawson & Glenn 2019 [14], (ii) HPVs by Ren et al (2019) [15], (iii) EBV Lawson et al 2018 [1], (iv) BLV by Buehring & Sans 2019 [16]. The details in these case control studies have been included as Supplementary Tables.…”
Section: Methodsmentioning
confidence: 99%
“…Reviews of case control studies of viruses and breast cancer have been previously conducted. These include (i) MMTV by Lawson & Glenn 2019 [14], (ii) HPVs by Ren et al (2019) [15], (iii) EBV Lawson et al 2018 [1], (iv) BLV by Buehring & Sans 2019 [16]. The details in these case control studies have been included as Supplementary Tables.…”
Section: Methodsmentioning
confidence: 99%
“…Purified genomic DNA from each sample was analyzed for HPVs, EBV, and MMTV-like virus by polymerase chain reaction (PCR) using specific primers for high-risk HPV types: 16,18,31,33,35,39,45,51,52,56,58,59, 66 and 68 as well as EBNA1, EBNA2 (Forward primer: 5′-AGGGATGCCTGGACACAAGA-3′ and Reverse primer: 5′-TTGTGACAGAGGTGACAAAA-3′) and LMP1 of EBV as previously described. 50,51 In addition, PCR was performed for MMTV (Forward primer: 5′-GATGGTATGAAGCAGGATGG-3′ and Reverse primer: 5′-CCTCTTTTCTCTATATCTATTAGCTGAGGTAATC-3′).…”
Section: Polymerase Chain Reaction Analysismentioning
confidence: 99%
“…[35][36][37][38] However, a few studies failed to detect the presence of these oncoviruses in human breast cancer as well as normal mammary tissues. [39][40][41] Based on previous reports depicting the role of HPVs, EBV, and MMTV-like virus in the initiation of various cancers, comprising breast, 19,30,[36][37][38][42][43][44][45] we explored the presence/co-presence of high-risk HPVs, EBV, and MMTV-like virus in TNBC samples in Croatian women.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [19] were able to isolate a complete provirus from human BC samples and Lawson et al [20] found MMTV-like antigens and sequences in benign lesions from women that developed BC years later. Furthermore, MMTV-like sequences were found in other human biological samples, such as milk [21], saliva [22], and peripheral blood lymphoid cells [23,24], suggesting that viral transmission and spreading in humans are similar to that described in mice, occurring via breast-feeding and infection of mucosa-associated lymphocytes before reaching the breast tissue [25].…”
Section: Introductionmentioning
confidence: 95%